TECNOLOGIA ASSISTIVA E INCLUSÃO DE ESTUDANTES COM PARALISIA CEREBRAL: UM ESTUDO PRELIMINAR - Samuel Vinente; Ketlen Júlia Lima da Silva (Universidade do Oeste Paulista, 2016)
This paper presents a theoretical study that aimed to analyze the use of Assistive Technology (AT) as a facilitator in the process of school inclusion of children with cerebral palsy (CP). It conducted a literature review in the Bank of Theses and Dissertations Portal of the Public Domain of Higher Education Personnel Training Foundation (CAPES), covering the period 2005 to 2010. The following descriptors were used: cerebral palsy; technical aids; educational resources; accessibility; Assistive technology; alternative communication; additional communication; augmentative communication; augmentative and alternative communication; alternative and expanded communication; strategies and teaching strategies. Based on the descriptors were selected 195 works, of which 167 were excluded because they repeated or do not meet the objectives of the study, remaining 28. The results indicated the years with greater expressiveness in the publication: 2007 (eight studies); followed respectively by 2009 (six papers); 2008 (five papers); 2010 (five papers); and 2006 (only four). It can be seen that 86% of works have been published in southeastern institutions, 11% in the Northeast and 3% in the south. Of these, 71% resulted from research master's and 29% of doctoral research. The authors point out the need for specialized training for educators who work with students who have PC and appropriateness of the physical structure of schools to promote accessibility. It is hoped that this study will contribute in the production and socialization of knowledge in the field of research in special education, providing new perspectives on school inclusion.